(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Volga’s The Liberation of Sita is a compelling exploration of the untold stories and voices of women in the epic Ramayana. Within this narrative, the concept of sisterhood emerges as a powerful force, challenging traditional patriarchal norms and giving voice to the suppressed experiences of women.